1996
DOI: 10.1037/0893-3200.10.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Assessing relationship standards: The Inventory of Specific Relationship Standards.

Abstract: The current study explored the importance of relationship standards in marital functioning through the use of a new self-report inventory: the Inventory of Specific Relationship Standards (ISRS). The findings indicate that community couples who hold relationship-focused standards (i.e., those who ask for a great deal from their marriages) score higher on all of the indixes of marital functioning than spouses with less relationship-focused standards. The results demonstrate that two pieces of information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 31 publications
2
88
1
2
Order By: Relevance
“…The interrelated constructs of power, dominance, and control are important aspects of interpersonal functioning and can be influenced by a combination of person, situation, and relationship factors (Baucom et al 1996;Burgoon and Dunbar 2000;Huston 1983). Huston (1983) characterizes power as the portion of influence over another's thoughts and behaviors that an individual generates intentionally, whereas dominance reflects the extent to which intentional or incidental influence between parties is asymmetrical.…”
Section: Are Wives Typically the Subordinate Marital Partner?mentioning
confidence: 99%
“…The interrelated constructs of power, dominance, and control are important aspects of interpersonal functioning and can be influenced by a combination of person, situation, and relationship factors (Baucom et al 1996;Burgoon and Dunbar 2000;Huston 1983). Huston (1983) characterizes power as the portion of influence over another's thoughts and behaviors that an individual generates intentionally, whereas dominance reflects the extent to which intentional or incidental influence between parties is asymmetrical.…”
Section: Are Wives Typically the Subordinate Marital Partner?mentioning
confidence: 99%
“…To the extent that high standards tend to be more characteristic of singles who are in a better position to find and attract good partners, it is not surprising that the association between the absolute stringency of spousal standards and successful partnering outcomes would be inconsistent and sometimes positive. Indeed, past work on relational standards has frequently shown that holding more stringent standards -in and of itself -is associated with better rather than poorer relationship outcomes (e.g., Baucom, Epstein, Rankin, & Burnett, 1996;Fletcher et al, 1999;Morrow & O'Sullivan, 1998;Murray, Griffin, & Holmes, 1996). By developing a model to more directly quantify the attainability of individuals' standards for a spouse, this research seeks to estimate more accurately the implications of spousal criteria for later marital behavior.…”
mentioning
confidence: 99%
“…For example, having higher expectations about one's romantic partner has been found to be associated with higher quality relationships (Baucom, Epstein, Rankin, & Burnett, 1996;Fletcher, Simpson, & Thomas, 2000). However, this relation holds only when the aspirations are met, when they are not inordinately high, and when relationship partners have positive relationship skills (McNulty & Karney, 2004).…”
Section: Maintain Reasonable Aspirationsmentioning
confidence: 91%